A Century of Variance. Issue 4 (26th July 2018) - Charlesworth, Brian; Edwards, Anthony W. F.
Abstract: Brian Charlesworth and Anthony W. F. Edwards mark the 100th anniversary of a paper by R. A. Fisher, which introduced the statistical term "variance". What followed was a whole new field of statistical analysis